Development and validation of a prognostic score for TIPS placement in patients with viral hepatitis cirrhosis-related portal hypertension: a multi-center retrospective study - Que, Zenglong; Wu, Mingsong; Lai, Shujie; Wang, Lei; Mu, Zhiyong; Yang, Jinhui; Xiong, Wei; Hu, Hong; Liu, Aimin; An, Xuan; Yu, Haodong; Cao, Qin; et al. (Frontiers in Medicine, 2024)
Introduction There is no established scoring model focused on viral hepatitis patients to predict the prognosis after transjugular intrahepatic portosystemic shunt (TIPS). We aimed to develop and validate a novel model based on the largest cohort for better prediction of both short-term (1 year) and long-term (3 years) postoperative prognoses after TIPS in viral hepatitis cirrhosis-related portal hypertension patients. Methods A total of 925 viral hepatitis cirrhosis-related portal hypertension patients who underwent TIPS from nine hospitals were divided into the training and external validation cohorts. A novel Viral-associated Index of Post-TIPS score (VIPs) model was developed after performing Cox regression analysis. The VIPs model was compared to five previous models, namely, Child–Pugh, MELD, ALBI, CCG, and FIPS. Furthermore, X-tile software was used to stratify patients into low-, medium-, and high-risk groups. Results The VIPs model included age, ascites, albumin, prothrombin time, total bilirubin, and sodium for post-TIPS prognosis prediction. The model demonstrated satisfying predictive efficiency in both discrimination and calibration, with an area under the curve of 0.781/0.774 (1 year/3 years) in the training cohort and 0.771/0.775 (1 year/3 years) in the external validation cohort, respectively. Discussion We first developed and externally validated a novel VIPs model for better prediction of both short-term and long-term postoperative prognoses after TIPS in Chinese patients with viral hepatitis cirrhosis-related portal hypertension.